Pengaruh Penggunaan Knalpot Standart Dengan Racing Terhadap Torsi Dan Daya Sepeda Motor Yamaha Aerox 155CC Tahun 2018 - Saeful Rohim; Anis Lathifudin; Syarif Hidayat; Cahyo Pono Sasmito; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
The exhaust is part of the exhaust on the motorbike which is designed for exhaust gas exhaust paths and as a motor silencer. The exhaust system or often called the exhaust has an important role in the function of the exhaust (muffler) as a silencer and regulates the direction of flow of combustion gases so that they flow regularly. This study aims to examine the effect of exhaust changes on torque and power or performance of Aerox 155cc motorbikes. The maximum torque of the standard exhaust is 11.36 N.m and the power is 11.01 HP. On the racing exhaust, the torque is 11.14 N.m with a power of 11.33 HP. Changes in the exhaust affect motorcycle performance but not significantly.